2003
DOI: 10.1063/1.1609936
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive phase transitions in ferroelectrics and antiferroelectrics

Abstract: In this paper, we present a microscopic model for heterogeneous ferroelectric and an order parameter for relaxor phase. We write a Landau theory based on this model and its application to ferroelectric PbFe$_{1/2}$Ta$_{1/2}$O$_3$ (PFT) and antiferroelectric NaNbO$_3$:Gd. We later discuss the coupling between soft mode and domain walls, soft mode and quasi-local vibration and resulting susceptibility function.Comment: 6 pages, Fundamental physics of ferroelectrics 200

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…At x ≈ 0.1, NNG exhibits a jump to a state where the hysteresis disappears (figure 1, curve 3). A qualitative explanation of this phenomenon has been given in terms of stresses and fields introduced by Gd [11].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…At x ≈ 0.1, NNG exhibits a jump to a state where the hysteresis disappears (figure 1, curve 3). A qualitative explanation of this phenomenon has been given in terms of stresses and fields introduced by Gd [11].…”
Section: Introductionmentioning
confidence: 98%
“…The explanation of the experimental results obtained can be given in the same way as for relaxors [1,2]. One can introduce a distribution function for the Curie temperatures, f (T c ), which, in the simplest case, can be described by a Gaussian function (this distribution is caused by internal local fields and stresses introduced by impurities [7,8]):…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…for a wide variety of ferroelectric materials 23 . First principles frozen phonon studies for various ordered supercells in PMN have been reported previously by Prosandeev et al 30,31 using ultrasoft pseudopotentials. We have built on the previous work by performing first-principles lattice dynamics computations including LO-TO splittings, and have studied a variety of different structures, following a cascading set of soft modes towards the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…First principles theoretical calculations [24][25][26][27][28][29][30][31][32][33][34][35][36][37] using all electron LAPW [24][25][26][27][28][29] as well as plane wave basis sets and pseudopotentials [30][31][32][33][34][35] have been successfully used to understand fundamental aspects related to crystal structure, bonding and ferroelectric properties 24 , spontaneous polarization and piezoelectric constants [25][26][27]37 , polarization rotation and observed high electromechanical coupling coefficients 25,26 , frozen phonon [29][30][31] and linear response studies 28,32,33 , structural response to macroscopic electric fields 36 , etc. for a wide variety of ferroelectric materials 23 .…”
Section: Introductionmentioning
confidence: 99%